(untitled) (Economics and region, 2025)
The article examines the terminological and institutional aspects of the development of the construction sector in Ukraine, which are of great importance for the formation of the modern regulatory and economic framework of the industry. The approaches to the use of the term "complex" in construction, which is traditionally used in three formats: as a component of the name of a construction object, as a separate type of object and as a launch complex, are analyzed. The discrepancy between the widespread use of the term in practice and its regulatory definition in current documents is emphasized. A comparative analysis of the concepts of "launch complex" and "construction queue" is carried out, which allows us to more clearly determine the specifics of project documentation and the procedure for commissioning objects. Particular attention is paid to the characteristics of the construction sector as a component of the economic system, its relationship with the construction market and the investment environment. The key actors of the construction market are identified: investors, customers, contracting organizations, manufacturers of building materials, machine-building enterprises and research institutes. The infrastructure of the construction market, which includes banks, exchanges, investment companies, auditing and consulting structures, is analyzed. The destabilizing factors of the functioning of the industry are emphasized: low investment attractiveness, imperfect regulatory framework, shortage of highly qualified personnel, dependence on imported equipment and materials. The article substantiates that effective development of the construction sector is possible only under the condition of a comprehensive institutional transformation, which includes modernization of the regulatory framework, improvement of the quality of education and professional training of personnel, creation of a favorable investment climate and stimulation of domestic production. It is proved that the construction complex should become a flexible and integrated system that combines public, social and commercial interests, which will allow Ukraine to reach a new qualitative level in the construction sector and ensure its competitiveness in the international market.